2016
DOI: 10.1038/srep29726
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic defect structure of exfoliated MoS2 single layers revealed by Scanning Tunneling Microscopy

Abstract: MoS2 single layers have recently emerged as strong competitors of graphene in electronic and optoelectronic device applications due to their intrinsic direct bandgap. However, transport measurements reveal the crucial role of defect-induced electronic states, pointing out the fundamental importance of characterizing their intrinsic defect structure. Transmission Electron Microscopy (TEM) is able to image atomic scale defects in MoS2 single layers, but the imaged defect structure is far from the one probed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
243
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(275 citation statements)
references
References 35 publications
31
243
1
Order By: Relevance
“…First, what is the nature of the defect-related PL feature (D peak)? It has been attributed both to two-and three-particle states as well as to various defect types 18,20,21,[27][28][29][30] . Second, can the D peak be used as an indicator of a sample quality, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…First, what is the nature of the defect-related PL feature (D peak)? It has been attributed both to two-and three-particle states as well as to various defect types 18,20,21,[27][28][29][30] . Second, can the D peak be used as an indicator of a sample quality, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it has been shown that single sulfur atom vacancies are the dominant defects in the exfoliated single layer of MoS 2 , generating similar states in the bandgap. 28 At low temperatures where the Fermi distribution is close to the step-like function, less charges will be captured by the S-vacancy-induced energy state due to losing thermal energy, causing E F to move towards the mid-gap level (the band structure at 10 K is shown in Fig. S5 in the supplementary material).…”
Section: à3mentioning
confidence: 99%
“…Further localized perturbations may come from structural defects, for example Sulfur vacancies, which cause mid‐gap states in MoS 2 . These mid gap states have triangular and hexagonal atomic scale patterns observed recently in STM measurements . Ghorbani et al analysed the effect of different localized defects on the MoS 2 transport for currents in the zigzag‐ and armchair directions, utilizing a nonequilibrium Green function DFT approximation.…”
Section: Discussionmentioning
confidence: 99%